1978
DOI: 10.1007/bf02586701
|View full text |Cite
|
Sign up to set email alerts
|

Osseous metastases from carcinomas of the colon and rectum

Abstract: Of 765 patients with disseminated metastatic carcinoma of the colon and rectum treated at Memorial Sloan-Kettering Cancer Center during the ten-year period 1960--1970, 53 (6.9 per cent) had skeletal metastases. Of these, 14 (1.8 per cent) had osseous metastases only. In one case the osseous lesion was the first symptom of a cancer of the sigmoid colon, and one patient had metastasis in the fibula from a primary rectal cancer. In our series the incidences of osseous metastases were 8.9 per cent from rectal carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0
12

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 17 publications
3
40
0
12
Order By: Relevance
“…Over 36 years, only 41 patients at our institution, out of a total of 35,543 cases of colorectal carcinoma (0.1%), required surgery for skeletal metastases. Our patient numbers and proportions agree with clinical series reported by others [4,5,10,12,13,[15][16][17]22] . Consequently, prognostic factors following surgery for bone metastases are not well understood.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Over 36 years, only 41 patients at our institution, out of a total of 35,543 cases of colorectal carcinoma (0.1%), required surgery for skeletal metastases. Our patient numbers and proportions agree with clinical series reported by others [4,5,10,12,13,[15][16][17]22] . Consequently, prognostic factors following surgery for bone metastases are not well understood.…”
Section: Discussionsupporting
confidence: 92%
“…The disease free interval from primary colorectal diagnosis to the onset of bone metastasis in this study (median of 26 months) is comparable to other reported series [15,16] . The overall incidence of osseous metastases from primary tumors of the gastrointestinal tract has been reported as ranging from 1-10.5 percent [1,18] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our patient presented with neck pain due to cervical spine metastasis as the primary manifestation of occult colorectal carcinoma, which had not been diagnosed previously. In the series reported by Besbeas and Stearns [5], rectal carcinoma metastasized to bone more frequently than did colonic carcinoma (8.9 and 5.1%, respectively). This difference might relate to differences in anatomical position and venous drainage, because rectal tumors lie adjacent to the paravertebral venous plexus [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Also comparing between various histological types, signet ring cell carcinoma shows a high incidence of bone metastasis. 1,5,6 The most common sites of osseous metastases are the vertebrae, pelvis and sacrum. Osseous metastases in these sites are blood-borne through veins, and the paravertebral venous plexus of Batson.…”
Section: Discussionmentioning
confidence: 99%